2001
DOI: 10.1007/s002210100682
|View full text |Cite
|
Sign up to set email alerts
|

Human EEG responses to 1?100�Hz flicker: resonance phenomena in visual cortex and their potential correlation to cognitive phenomena

Abstract: The individual properties of visual objects, like form or color, are represented in different areas in our visual cortex. In order to perceive one coherent object, its features have to be bound together. This was found to be achieved in cat and monkey brains by temporal correlation of the firing rates of neurons which code the same object. This firing rate is predominantly observed in the gamma frequency range (approx. 30-80 Hz, mainly around 40 Hz). In addition, it has been shown in humans that stimuli which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

88
834
7
12

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 919 publications
(941 citation statements)
references
References 30 publications
88
834
7
12
Order By: Relevance
“…Steady-state fields sessions 2 and 3 for which the percentual errors are Oscillatory visual stimulation results in so-called steadyindicated in parentheses as computed from the difference state responses of the visual cortex reflecting the frequency of presented to perceived reversals. Since in session 2 the of stimulation [17,60]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Steady-state fields sessions 2 and 3 for which the percentual errors are Oscillatory visual stimulation results in so-called steadyindicated in parentheses as computed from the difference state responses of the visual cortex reflecting the frequency of presented to perceived reversals. Since in session 2 the of stimulation [17,60]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it would not be expected to reveal activity associated with perceptual completion in neuronal populations that are not strongly driven by retinal input (16), such as those outside occipital cortex. Importantly, we found that target-specific responses were reduced but not eliminated during filling-in.…”
Section: Discussionmentioning
confidence: 99%
“…Data were band-pass filtered at 1-45 Hz (Butterworth) and from each of the time periods defined by subject responses, consecutive, nonoverlapping 500-ms epochs were extracted from the time series. Each epoch was extracted exactly at one of the trigger events, where the target changed from black to white, to ensure phase-locked averaging (16), with epochs starting 100 ms before the trigger and lasting until 400 ms after the trigger. Because epochs were nonoverlapping, not every trigger was used as a start point to extract data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SSVEPs are a phase-locked brain response triggered by fixing the user's gaze upon a repetitive visual stimulus (RVS) such as a flashing light [8], or a reversing pattern [9]. The SSVEP is produced by groups of neurons which output a repetitive signal matching the RVS frequency, maintained for the duration of the fixation period.…”
Section: Introductionmentioning
confidence: 99%